THE ATTRACTION AND SELECTION OF ACCOUNTING MAJORS. - Moyer, C. A. (The Accounting Review, 1956)
Abstract This article presents information on the graduates entering into the field of accounting. It appears likely that very soon the departments of accountancy will not be concerned with the attraction of more students but instead they will be concerned with the problem of handling the large number of students who want to major in accountancy. Universities should expect in the near future to be forced to consider proper means of restricting enrollment in the field of accountancy. The profession should be given adequate representation at "career days" in high schools and colleges. Many high schools and colleges set aside one or more days of each year to acquaint students with the various professions and occupations available to them. Vocational guidance advisors, deans of men, placement officers, and other non-accountants are no doubt sincere in their efforts to counsel, but they often give a distorted or inaccurate picture to interested students. Accountants should seek every opportunity to participate in these career, days or vocational guidance programs. Every school, which has a curriculum in accountancy, should have an accountancy club or a similar organization to sponsor activities, which are usually carried on by such a group. An accountancy club is ordinarily open to any student in a college of commerce who has had one year of accounting. Its purpose is to acquaint students with the various types of opportunities available in accounting, to bring them in contact with leaders in the field, to establish a good student-faculty relationship, to give students training in leadership, and to supply them with information.